2020
DOI: 10.1080/1828051x.2020.1748526
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of non-genetic effects for measures of hunting performance in short-haired and rough-haired Italian hound

Abstract: Renieri (2020) Estimates of non-genetic effects for measures of hunting performance in short-haired and rough-haired Italian hound,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Rating scales are used across numerous fields to assess differences between individuals (human and animal), e.g., in the occurrence of particular behaviors or medical conditions ( 1 , 2 ), the degree of pain experienced (or inferred in the case of animals) ( 3 , 4 ), mood and quality of life ( 5 7 ), marketing preferences ( 8 , 9 ), as well as being widely used to assess performance in specific tasks or roles ( 10 , 11 ). They are used widely when quantifying the performance of working dogs both in selection tests [e.g., ( 12 14 )] and in their working role [e.g., ( 15 , 16 )].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rating scales are used across numerous fields to assess differences between individuals (human and animal), e.g., in the occurrence of particular behaviors or medical conditions ( 1 , 2 ), the degree of pain experienced (or inferred in the case of animals) ( 3 , 4 ), mood and quality of life ( 5 7 ), marketing preferences ( 8 , 9 ), as well as being widely used to assess performance in specific tasks or roles ( 10 , 11 ). They are used widely when quantifying the performance of working dogs both in selection tests [e.g., ( 12 14 )] and in their working role [e.g., ( 15 , 16 )].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst some studies explore predictors of successful acceptance into training ( 27 ), other explore predictors of successful certification ( 23 ), binary outcomes, which although practically very important, lack granulation. Other studies rely on scales devised by the working dog organization, such as those used in competitive hunting trials ( 16 ), which were often formed historically without scientific input and without thorough consideration of how their design may influence potential sources of error and the quality of information obtained. There is considerable evidence that seemingly small changes in scale design can alter the way raters interpret and use scales, therefore affecting the reliability and validity of data ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Temperament and selection tests have received considerable focus, with researchers, for example, exploring which behaviors in adult dogs and puppies best predict success as a detection dog [e.g., ( 5 8 )], police dog ( 9 ), guide dog ( 10 12 ), or hunting dog ( 13 ). These studies have required researchers to measure the behavioral variability between individual animals, and there has been a large amount of effort developing adequate instrumentation that is both reliable and valid ( 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, when seeking to predict working dog success, or explore factors that may influence that success, there has been less focus on validating measures of success or performance. Some studies have quantified the proportion of targets found in a single standardized search task ( 18 20 ), but most have relied on training organizations' own long-established ratings of performance [e.g., ( 13 , 19 , 21 , 22 )], or used pass/ fail at selection ( 6 ) or certification ( 23 ) as measures of success. These approaches ensure that the outcomes of the studies have great practical relevance and validity and enable individuals responsible for training working dogs to determine predictors of successful training.…”
Section: Introductionmentioning
confidence: 99%